2017
DOI: 10.1039/c6ra25372e
|View full text |Cite
|
Sign up to set email alerts
|

Novel iron doped calcium oxalates as promising heterogeneous catalysts for one-pot multi-component synthesis of pyranopyrazoles

Abstract: The co-precipitation method using a surface modifier, glutamic acid was employed in the design of iron doped calcium oxalates (Fe-CaOx). Fe-CaOx with diverse iron loading (0.5-3.0 mmol) were prepared and their phase purity and surface features were examined by X-ray powder diffraction (XRD), Fourier transform infrared (FT-IR), electron microscopy (SEM, TEM), energy dispersive X-ray (EDX), Inductively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 49 publications
(23 reference statements)
0
22
0
Order By: Relevance
“…From the previously reported works, the following mechanism (Scheme ) was proposed. In the presence of PBCMO‐amine catalyst, the aldehyde reacted with malononitrile to form a Knoevenagel product 4a.…”
Section: Resultsmentioning
confidence: 99%
“…From the previously reported works, the following mechanism (Scheme ) was proposed. In the presence of PBCMO‐amine catalyst, the aldehyde reacted with malononitrile to form a Knoevenagel product 4a.…”
Section: Resultsmentioning
confidence: 99%
“…218 The authors claimed the superiority of the Fe 3 O 4 @SiO 2 -HMTA-SO 3 H-catalyzed synthesis considering its faster and greener reaction with good yields and feasible recovery of the catalyst assisted by an external magnet compared to other reported protocols. [219][220][221] However, the recyclability of the catalytic system was found to decrease signicantly aer the fourth catalytic cycle. Salehzadeh et al reported the catalytic use of a molybdenum Schiff-base complex supported on Fe 3 O 4 @SiO 2 NPs for the synthesis of pyranopyrazoles using different approaches mediated by benzaldehyde, malononitrile, and 3methyl-1-phenyl-2-pyrazolin-5-one under solvent-free conditions at rt.…”
Section: Fenp-catalyzed Synthesis Of Heterocyclesmentioning
confidence: 99%
“…In 2017, Gangu et al 108 applied Fe-CaO x materials as recyclable heterogeneous catalysts for the synthesis of 2,4-dihydropyrano[2,3-c]pyrazoles (49) via four component condensation of aromatic aldehydes, malononitrile, hydrazine hydrate and dimethyl acetylenedicarboxylate in ethanol with high yields (92-98%) and short reaction times (<20 min) (Scheme 72). The authors prepared Fe-CaOx catalysts by co-precipitation technique using glutamic acid as an additive for crystal growth inhibition.…”
Section: Using Inorganic Catalystmentioning
confidence: 99%